The Main Directions of The Scientific Reform in Republic of Moldova - Natalia, Percinshi; Aurelia, Turcan (Susu) (International Business and Accounting Research Journal, 2017)
The article reflects the issues about reforming the Moldavian Science. The author reveals some priorities of the Strategy of Science Evolution Moldova - 2020, which is aimed at the efficient use of intellectual potential by stimulating innovation, human capital consolidation and attraction of young researchers to develop research capacity in high schools and universities.